Kajian Beberapa Tumbuhan yang Digunakan dalam Pembuatan Bahan Baku Nitroselulosa Propelan - Muna, Arifa Fikriya Zaharol; Dacosta, Fransisca Clodina; Aritonang, Sovian (Universitas Muhammadiyah Surakarta, 2020)
Propellant is one of the national industries development program. Raw material of double base propellant is nitrocellulose and nitroglycerin. Nitroglycerin approved by country, but nitrocellulose still relies on imports. The need for nitrocellulose continues to increase and independence in the manufacture is very necessary to support alusista independence. Therefore, it is necessary to map the types of local plants needed to produce nitrocellulose. Method of this research is carried out a discussion from literature by tracing and collecting data taken with various references about plant which has potential as raw material for making nitrocellulose. The data collected is described as information describing plant species with the highest potential forproducing nitrocellulose. There are several plants that can produce nitrocellulose, including sago (Metroxylon sago Rottb.), Cotton (Gossyoium sp.), Kapok (Ceibe Petandra), Palm Oil (Arecaceae), Aren (Arenga pinnata), Pineapple (Ananas comosus) and Bamboo Beema (Bambusa balcoa). Most nitrocellulose by the process of nitration produced by cottonwood plants with levels reaching 50%. Several other types of plants have cellulose content. Most of the higher alpha cellulose include acacia (Acasia mangium), kenaf (Hibiscus cannabinus), Mangrove (Rhizophora) and banana klutuk (Musa balbisiana colla). Plants that have high cellulose content specially alpha cellulose content, can be using with chemically nitration processed to produce nitrocellulose. Further research is still needed to maximize the yield of nitrocellulose in local plants.